2022
DOI: 10.1101/2022.11.22.517103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host translation machinery is not a barrier to phages that infect both CPR and non-CPR bacteria

Abstract: Within human microbiomes, Gracilibacteria, Absconditabacteria, and Saccharibacteria, members of Candidate Phyla Radiation (CPR), are increasingly correlated with human oral health and disease. We sought phages that are capable of infecting these bacteria, as these may prove effective for phage therapies to control oral microbiome composition. To do this we analyzed spacer inventories from CRISPR-Cas systems that themselves could be used for phage editing. Absconditabacteria and Gracilibacteria recode the typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…The simultaneous compatibility with both genetic codes suggested that this phage probably has a larger host range. Liu et al recently reported other phages that can also employ both genetic codes, suggesting a potential to infect both Patescibacteria and other bacteria (18). The differential translation of some genes could constitute a host-dependent regulation mechanism.…”
Section: Crispr-based Identification Of a Jumbo Phage Targeting S Met...mentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous compatibility with both genetic codes suggested that this phage probably has a larger host range. Liu et al recently reported other phages that can also employ both genetic codes, suggesting a potential to infect both Patescibacteria and other bacteria (18). The differential translation of some genes could constitute a host-dependent regulation mechanism.…”
Section: Crispr-based Identification Of a Jumbo Phage Targeting S Met...mentioning
confidence: 99%
“…A few studies have established links with phage genomes using CRISPR spacers found in patescibacterial genomes. For example, Paez-Espino et al identified 17 putative patescibacterial phages (17), and Liu et al recently reported the identification of 391 additional putative patescibacterial phages (18). Further efforts are required to comprehend the diversity and impact of phages on Patescibacteria.…”
Section: Introductionmentioning
confidence: 99%